HUBUNGAN INTELLECTUAL CAPITAL DENGAN KINERJA PERUSAHAAN - Achmad Arya Hudiyono Saputra (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
This study examines the relationship between intellectual capital and firm perfomance. This study is to prove that intellectual capital can be considered by management as a factor in improving frim performance. The population in this study are all those listed on the Indonesia Stock Exchange during the period 2014 to 2018 that has meet the criteria that have been determined. In this study, intellectual capital measured by using value added intellectual coefficient (VAIC™) method. The results suggest that the intellectual capital has a positive association with firm performance proxied with ROA and Tobin’s Q, implying that the intellectual capital help firm to increase it’s performance. This study supports the argument of resource based theory that if the intellectual capital can be managed properly by the firm, intellectual capital will increase competitive advantage for the firm and also can increase their performance.